2015
DOI: 10.1371/journal.pntd.0004041
|View full text |Cite
|
Sign up to set email alerts
|

Pathogen- and Host-Directed Antileishmanial Effects Mediated by Polyhexanide (PHMB)

Abstract: BackgroundCutaneous leishmaniasis (CL) is a neglected tropical disease caused by protozoan parasites of the genus Leishmania. CL causes enormous suffering in many countries worldwide. There is no licensed vaccine against CL, and the chemotherapy options show limited efficacy and high toxicity. Localization of the parasites inside host cells is a barrier to most standard chemo- and immune-based interventions. Hence, novel drugs, which are safe, effective and readily accessible to third-world countries and/or dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 52 publications
5
27
0
2
Order By: Relevance
“…Guanidine-based antimicrobials were thus believed to have low toxicity to humans (Ikeda et al, 1983(Ikeda et al, , 1984. However, recent accounts have reported PHMB penetrating mammalian cells and interacting with chromosomes, raising concerns about health hazards from guanidine-based antimicrobials (Allen et al, 2004(Allen et al, , 2006Chindera et al, 2016;Firdessa et al, 2015).…”
Section: Biocidal Properties Of Phmg-pmentioning
confidence: 99%
“…Guanidine-based antimicrobials were thus believed to have low toxicity to humans (Ikeda et al, 1983(Ikeda et al, , 1984. However, recent accounts have reported PHMB penetrating mammalian cells and interacting with chromosomes, raising concerns about health hazards from guanidine-based antimicrobials (Allen et al, 2004(Allen et al, , 2006Chindera et al, 2016;Firdessa et al, 2015).…”
Section: Biocidal Properties Of Phmg-pmentioning
confidence: 99%
“…Antimicrobial polymers appear much less susceptible to acquired resistance, and they can be surprisingly effective against intracellular pathogens. For example, we recently reported that a cationic polymer, polyhexamethylene biguanide (PHMB) ( Figure 1 ), effectively killed intracellular S. aureus inside keratinocytes and the parasite Leishmania in macrophages, through a dynamin dependent uptake mechanism ( Firdessa et al, 2015 ; Kamaruzzaman et al, 2016 ). Therefore, we considered that PHMB might also be effective against intracellular S. aureus within bovine mammary epithelial cells.…”
Section: Introductionmentioning
confidence: 99%
“…PHMB is able to enter a range of cell types, including many mammalian cells (Firdessa et al, , Chindera et al, ). Moreover, following mammalian cell entry, PHMB co‐localizes with intracellular MRSA inside the host cells (Kamaruzzaman et al, ).…”
Section: Novel Promising Therapies In the Treatment Of Intracellular mentioning
confidence: 99%